Удосконалення методичних засад управління витратами на промислових підприємствах - Яковлєв, Анатолій Іванович (Аудиторська фірма "Аналітик", 2014)
Розглянуто основні причини високого рівня витрат на виробництво продукції промислових підприємств. Окреслено напрямки ефективного управління витратами на сучасному етапі господарювання. Обумовлено виокремлення сталого та умовно сталого компонентів величини постійних витрат при оцінці граничних витрат.

Considered the main causes of the high level of the cost of production of products of industrial enterprises. Defined areas of the effective cost management at the present stage of economic management. Developed to the isolation of the stable and conditionally stable componentі of value of fixed costs in assessing the marginal costs.
The improvement of methodological foundations of managing costs at industrial enterprises
Keywords: витрати; промислові підприємства; граничні витрати; постійні витрати; облік; моніторинг; costs; industrial enterprises; fixed costs; accounting; monitoring